Penerapan Game Edukasi Geograpiea Untuk Meningkatkan Hasil Belajar Siswa SD - Mega Andini Putri; Eneng Mufadillah; Laelatul Fajriah (Proseding Didaktis: Seminar Nasional Pendidikan Dasar, 2021)
Today's rapid growth in technology and communication has affected the Indonesian education aspect. An educator is expected to be able to use the technological advances, especially in the learning process in class. One is to use an instructional tool or video-based learning medium on a gadget. The study studied geographya games. As one of the digital age teaching media for the need for elementary school children in order to better understand geography. The study USES qualitative methods with a descriptive approach to library studies. The study showed a result that geograpiea games were able to help students better understand the learning of the region in Indonesia.